Disentangling the role of the rhizobacterium Azospirillum brasilense on Zea spp. defenses against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Cabral, Isabella Rubio (2026)
Interactions between plants and soil-dwelling organisms play a central role in shaping both above- and belowground ecological communities. These interactions are further influenced by plant domestication, which can alter rhizosphere microbial assembly and function, with cascading effects on plant phenotypes and interactions across higher trophic levels. Although numerous studies have examined the influence of beneficial microbes on plant defenses against herbivores, the effects of the plant growthpromoting rhizobacterium (PGPR) Azospirillum brasilense on maize and its wild relatives remain poorly understood, particularly within a multitrophic context. In this dissertation, we examined the cascading effects of the association between A. brasilense, cultivated maize (Zea mays), and the wild relative Zea luxurians on the herbivore Spodoptera frugiperda and its larval parasitoid Aleiodes ceres. Specifically, we evaluated how PGPR inoculation influences plant defense-related traits, herbivore performance and behavior, parasitoid attraction, and plant volatile organic compound emissions. Across both maize and teosinte, inoculation with A. brasilense enhanced fall armyworm larval performance, indicating that microbial associations can increase host suitability for herbivores. At the same time, parasitoids exhibited stronger attraction to inoculated plants, demonstrating that PGPR-mediated changes can also enhance indirect plant defenses. In maize, PGPR inoculation reduced oviposition by adult moths under no-choice conditions, whereas oviposition preference in Z. luxurians was not affected by microbial association. These patterns were supported by qualitative shifts in plant volatile emissions, suggesting that rhizobacterial inoculation modulates signaling pathways involved in plant-insect interactions. Contrary to expectations based on wild ancestry, Z. luxurians did not exhibit enhanced resistance to fall armyworm attack in the absence of microbial association. Collectively, these results highlight the context-dependent nature of plant-microbe-insect interactions and underscore the ecological relevance of belowground symbionts in shaping both direct and indirect plant defenses in domesticated and wild systems.